The Northeast : a fire survey - Pyne, Stephen J., 1949- (Pyne, Stephen J., 1949- To the last smoke, 2019)
"This book provides a thoughtful look at how the Northeast has experienced fire and the region's significance to the country's current wildfire-fighting efforts"--Provided by publisher